The theoretical level of economic judgment and the current state of economic science (Journal of Economic Research & Business Administration, 2015)
The paper is regarded as the economic theory of the generalized system of knowledge, describing and explaining the economic reality, and general economic theory as a verbal model of the economic system as a whole. The need for a general theory of the economy generated practical needs. Formation of economic theory is based on the generalized abstract concept, which gives the opportunity to operate formalized values. The cost is a basic abstract category, with various interpretations, which connected contemporary issues of the world economy and the international monetary system.
Keywords: generalization; abstraction; economic theory; goods; money; price; value; law of value; a measure of value; a world currency